Legal Analysis of Dismissal of Land Deed Officials Based on Health Conditions in the Perspective of Legal Certainty - Pratama, Okky Wildhan; Widhiyanti, Hanif Nur; Wisnuwardhani, Diah Aju (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to analyze the criteria for the dismissal of Land Deed Officials (PPAT) based on health conditions from a justice perspective. The method used is normative legal research with a statutory and conceptual approach, analyzed using a perspective analysis through grammatical and systematic interpretation methods. The results of the study show that the rules for dismissing PPATs due to health reasons refer to Article 10 paragraph (2) letter b of Government Regulation Number 24 of 2016. This regulation does not provide a health recovery period for PPATs, unlike the provisions in the Notary Position Law which grants a three-year recovery period. In conclusion, this regulation creates the potential for injustice for PPATs due to the absence of an opportunity to recover before being dismissed. Regulatory changes are needed to create a balance between public interest and the protection of individual rights.